Gastric mucosal change after the eradication of Helicobacter pylori in patients at high risk for gastric cancers - Lim, Na Rae; Chung, Woo Chul (Frontiers in Medicine, 2025)
BackgroundEradication of Helicobacter pylori alone will not eliminate the risk of gastric cancer. There was no conclusive evidence that eradication therapy reduced the incidence of gastric cancer in patients with atrophic gastritis or intestinal metaplasia.Materials and methodsThis study was conducted from March 2010 to September 2022, and enrolled 1,789 consecutive patients who underwent endoscopic submucosal dissection for gastric mucosal dysplasia. Patients who underwent two or more procedures for simultaneous or metachronous gastric epithelial dysplasia as high-risk groups for gastric cancer, and were confirmed to have H. pylori infection at the time of the procedure were included. Patients who received eradication treatment and underwent endoscopic follow-up for at least 2 years were included. The control group included patients who underwent endoscopic treatment for simple low-grade dysplasia. We investigated whether endoscopy was performed between 1 and 2 years after successful eradication of H. pylori. The endoscopic findings investigated were diffuse atrophy (open type), fundal atrophy, map-like redness, patch redness, erosions (body/antrum), hematin, endoscopic reflux esophagitis, hematin, and duodenitis.ResultsIn univariate analysis, diffuse atrophy, map-like redness, and patchy redness at antrum after H. pylori eradication were statistically different. In multivariate analysis, map-like redness [p < 0.01, 95% confidence interval (CI) 1.83–7.59] and patchy redness at antrum (p = 0.02, 95% CI 1.11–4.74) observed were statistically more frequent in patients with synchronous-metachronous gastric dysplasia.ConclusionMap-like redness and patchy redness are newly identified endoscopic risk factors for gastric cancer in patients treated for H. pylori eradication.